Metallothionein-3 is a clinical biomarker for tissue zinc levels in nasal mucosa. Issue 5 (October 2021) - Suzuki, Masanobu; Ramezanpour, Mahnaz; Cooksley, Clare; Ogi, Kazuhiro; Psaltis, Alkis J.; Nakamaru, Yuji; Homma, Akihiro; Wormald, Peter-John; Vreugde, Sarah
Abstract: Objective: Recently, depleted tissue zinc levels were found in nasal mucosa from patients with chronic rhinosinusitis (CRS) in correlation with tissue eosinophilia, however, no clinical biomarkers for tissue zinc levels have been identified. Metallothionein-3 (MT3) is an intracellular zinc chelator and previous data showed MT3 mRNA levels to be reduced in CRS patients with nasal polyps (CRSwNP). In this study, we examined the correlation between MT3 expression and zinc levels in nasal mucosa and primary human nasal epithelial cells (HNECs) to investigate whether MT3 could be a clinical biomarker for tissue zinc levels. Method: Tissue was harvested from 36 patients and mounted on tissue micro-array (TMA) slides. MT3 expression and tissue zinc fluorescence intensity were measured at different areas within the mucosa (surface epithelium and lamina propria) and compared between controls, CRSwNP and CRS without nasal polyps (CRSsNP) patients. MT3 mRNA and protein expression were examined in zinc-depleted HNECs by qPCR and immunofluorescence microscopy. Results: MT3 expression in CRSwNP was significantly decreased in both surface epithelium ( p <0.001 to controls) and lamina propria ( p = 0.0491 to controls). There was a significant positive correlation between tissue zinc levels and MT3 expression in nasal mucosa ( r = 0.45, p = 0.007). In zinc-deplete HNECs, MT3 expression was significantly decreased at mRNA ( p = 0.02) and protein level ( p <0.01). There was a significant positive correlation between tissue zinc levels and MT3 expression within individual HNECs ( r = 0.59, p <0.001). Conclusions: MT3 expression reflects intramucosal zinc levels in both nasal mucosa and HNECs indicating MT3 could be used as a clinical biomarker for monitoring intracellular zinc levels in the nasal mucosa.